2020
DOI: 10.1111/ffe.13385
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dwell on thermomechanical fatigue in superaustenitic steel Sanicro 25

Abstract: Superaustenitic steel Sanicro 25 has been subjected to out‐of‐phase thermomechanical fatigue cycles with 10‐min dwell at peak temperature in the temperature range from 250°C to 700°C. The effect of the dwells on the cyclic response, internal structure and damage mechanism was studied. Cyclic hardening/softening curves, cyclic stress–strain curves and fatigue life curves were evaluated. The internal structure and nanoparticles representing the obstacles for dislocation motion were analysed and identified by ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It must be pointed out that the cracking of oxide layer gets accentuated under TMF compared with IF cycling due to an increased tendency for embrittlement in the oxide layers during low temperature cyclic deformation in every half‐cycle of TMF, which necessitates the consideration of cyclic oxidation behavior and the implication thereof on the damage evolution and failure 26 . The role of simultaneous interaction of oxidation and creep under TMF cycling is studied for Sanicro 25 alloy in an earlier study 32,42 which concluded that the grain boundary oxidation plays a decisive role in both the crack initiation and propagation under IP TMF compared with OP cycling. It is noteworthy to recall that OP TMF often proves more detrimental resulting in lower cyclic lives in the case of materials that are prone to severe oxidation, particularly ferritic Cr‐Mo steels and carbon steels, compared with IP TMF cycling 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be pointed out that the cracking of oxide layer gets accentuated under TMF compared with IF cycling due to an increased tendency for embrittlement in the oxide layers during low temperature cyclic deformation in every half‐cycle of TMF, which necessitates the consideration of cyclic oxidation behavior and the implication thereof on the damage evolution and failure 26 . The role of simultaneous interaction of oxidation and creep under TMF cycling is studied for Sanicro 25 alloy in an earlier study 32,42 which concluded that the grain boundary oxidation plays a decisive role in both the crack initiation and propagation under IP TMF compared with OP cycling. It is noteworthy to recall that OP TMF often proves more detrimental resulting in lower cyclic lives in the case of materials that are prone to severe oxidation, particularly ferritic Cr‐Mo steels and carbon steels, compared with IP TMF cycling 26 …”
Section: Discussionmentioning
confidence: 99%
“…The failure under TMF cycling generally occurs from a combination of low temperature plastic deformation and creep deformation and oxidation at high temperature. Influence of time‐dependent and time‐independent mechanisms to cyclic deformation and their adverse effects on the fatigue life for various types of SS base metal under TMF and IF cycling in different temperature ranges is well addressed in literature 20–25,33,35–42 . A recent study 43 on the strain controlled TMF behavior of a dual hardening steel reported a decrease in both the hardness and the cyclic life with increasing aging time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reversed set-up, with maximum temperature during tension and minimum temperature in compression, is termed in-phase (IP) TMF. The potential and behaviour of A-ASS in power plant applications with TMF characteristics have, to some extent, already been evaluated [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. From the studies of Nagesha et al and Kumar et al [ 12 , 13 ] ( T = 300–650 C), Petras et al [ 14 , 15 ] and Polák et al [ 16 ] ( T = 250–700 C), the IP-TMF condition was generally associated with grain boundary cracking originating from creep damage and oxidation due to the depletion of chromium caused by precipitation of chromium carbides.…”
Section: Introductionmentioning
confidence: 99%
“…The potential and behaviour of A-ASS in power plant applications with TMF characteristics have, to some extent, already been evaluated [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. From the studies of Nagesha et al and Kumar et al [ 12 , 13 ] ( T = 300–650 C), Petras et al [ 14 , 15 ] and Polák et al [ 16 ] ( T = 250–700 C), the IP-TMF condition was generally associated with grain boundary cracking originating from creep damage and oxidation due to the depletion of chromium caused by precipitation of chromium carbides. The OP condition was more susceptible to the surrounding environment, which yielded oxide surface cracking and transgranular propagation.…”
Section: Introductionmentioning
confidence: 99%